A feasibility study for a new one-day protocol for [99mTc]TcDTPA2- and [99mTc]TcDMSA2- renal scintigraphy on dilated and non-dilated pediatric patients: underlying rationale - Fabiana Trevisan; Beatriz Nascimento; Gabriel Chibana; Luciana Maeda; Marta Vila; Valquiria Yoshida; Norberto Aranha; Victor M. Balcão; José Martins Oliveira Júnior (Brazilian Journal of Radiation Sciences)
Purpose. This work aimed at evaluating the possibility of performing renal exams of dynamic renal (DRS) and static renal (SRS) scintigraphy on the same day (one-day protocol, ODP), exams that are currently performed in two days. Approach. 25 infants (50 kidneys) of both genders, aged 8.4 ± 5.9 years, underwent an F+20 DRS protocol with [99mTc]TcDTPA2- followed by [99mTc]TcDMSA2- administration for the performance of SRS images at 3, 6 and 24 h. Dynamic images (DRS) were classified as dilated (D), undetermined (U), and non-dilated (P). Static images (SRS) were classified as: depressed in accented degree (DA); depressed in moderate degree (DM); depressed in mild degree (DL) and normal (NL). Results. Out of the 25 patients (50 kidneys), 7 (14 kidneys) were excluded by functional exclusion, hence 18 patients (36 kidneys) were clinically compared regarding their static images after 3, 6 and 24 h, resulting in 33.0% of dilated and 66.7% non-dilated. Only two patients of the dilated group were classified as obstructed. At the group with non-dilated and dilated but non-obstructed kidneys, 100% of them had the same clinical classification at 6 and 24 h images. Conclusions. Performance of both DRS and SRS exams in a single day for pediatric patients, when medical requests are carried out jointly, is feasible in a population with or without dilatation, when the difference between dynamic and static images is of at least 6 h. Due to the small number of obstructed kidneys in this study, further evaluation in this population is needed.